Philosophy Of Chess Education: The Armenian Experience - Tanajyan, K. A.; Tanajyan, L. A. (Մանկավարժ հրատ․)
The article shows the experience and features of the introduction and development of the chess subject in the Republic of Armenia. The article is based on the analysis of materials, documents, and data obtained from expert interviews, observations of the educational environment. The experience of introducing chess is a new phenomenon in the education system of the Republic of Armenia, which has a tradition of about ten years. Such programs and projects are aimed at modernizing education, an index of accessibility, improving the quality of education. The Armenian model of including chess as an educational subject has a conceptual significance for the educational system, it is aimed at solving the following educational problems: It should be mentioned that Armenian chess education in the field of general education is currently at the stage of development, the stable foundations, and principles of which are firmly laid and pursue certain goals. We can say that the introduction of chess has required a wide range of human, cultural, and social potential. Հոդվածի նպատակն է ցույց տալ Շախմատ ուսումնական առարկայի ներդրման փորձն ու առանձնահատկությունները ՀՀ-ում: Շախմատի ներդրման փորձը ՀՀ կրթական համակարգում նոր երևույթ է, ունի շուրջ տաս տարվա ավանդույթ: Նման ծրագրերն ու նախագծերը միտված են կրթության արդիականացմանը, մատչելիության ցուցանիշի, կրթության որակի բարձարցման արդյունավետությանը: Հոդվածը հիմնված է փորձագիտական հարցարույցներից, կրթական միջավայրի դիտարկումներից ստացված նյութերի, փաստաթղթերի և երկրորդային տվյալների վերլուծության վրա: Հայաստանյան շախմատային կրթությունը հանրակրթության ոլորտում ներկայումս գտնվում է բուն զարգացման փուլում, որի կայուն հիմքերն ու սկզբունքները այլևս անխախտորեն դրված են և հետապնդում են որոշակիացված նպատակներ: Կարող ենք ասել, որ շախմատ ուսումնական առարկայի ներդրումը պահանջել է մարդկային, մշակութային, սոցիալական ներուժի լայն ներառում: Статья показывает опыт и особенности внедрения и развития шахматной дисциплины в Республике Армения. Статья основана на анализе материалов, документов и данных, полученных в ходе опросов экспертов, наблюдений образовательной среды. Опыт введения шахмат является новым явлением в системе образования Республики Армения, которая имеет традицию около десяти лет. Такие программы и проекты направлены на модернизацию образования, индекс доступности, повышение качества образования. Армянская модель включения шахмат в качестве образовательного предмета имеет концептуальное значение для системы образования и направлена на решение следующих образовательных проблем: Следует отметить, что армянское шахматное образование в области общего образования в настоящее время находится на стадии развития, прочные основы и принципы которого прочно заложены и преследуют определенные цели. Мы можем сказать, что введение шахмат потребовало широкого спектра человеческого, культурного и социального потенциала.
Keywords: Chess